Liksomoppdagerne i Antarktis - Aasheim, Stein P (Snø & ski: årbok, 2007)
Keywords: Sørishavet; ekspedisjoner

Antarktis : en eventyrlig seilas - Aasheim, Stein P; Nævra, Arne (NRK aktivum, 2007)
Keywords: Antarktis; dyreliv; geografi; historie; hvalfangst; populærvitenskap; reisebeskrivelser

Growth rate and its variability in erect Antarctic bryozoans - Barnes, David K. A.; Webb, Karen E.; Linse, Katrin (Polar Biology, 2007)
Climate is altering rapidly in parts of the Arctic and Antarctic but we know little about how marine organisms are responding to, or might respond to such changes. Knowledge of within-taxon variability is the vital context (currently missing) to interpretation of environmental signals. We investigated growth in six species and three genera of erect Antarctic bryozoans, an ideal model taxon to investigate such response. Cellarinella margueritae, C. nodulata, C. rogickae, C. watersi, Melicerita obliqua and Stomhypselosaria watersi, extended 3.4, 5.2, 4.6, 4.1, 4.9 and 4.5 mm year(-1) and synthesised 24, 55, 45, 176, 34 and 46 mg CaCO3 year(-1), respectively. The maximum ages of these species ranged from 11 to 15 years except M. obliqua, which reached 32 years. This is the first investigation of growth rates of closely related Antarctic invertebrate species and reports the slowest growth rates of bryozoans known from anywhere to date. Our data coupled with that from literature shows that Antarctic bryozoan growth varies << 10(1) between species, 10(1) between genera, 10(2) between morphologies and is similar to 10(1) slower than in tropical or temperate regions. However, within encrusting types the slowest growing species grow at similar rates from poles to tropics. Age was a strong confounding factor across our Antarctic study species but age-standardised data showed a possible decline in annual growth from 1992 to 2003. We identify several factors increasing this environmental signal strength, including (1) the importance of generic (though not necessarily species) identification and (2) use of dry-mass or ash-free dry-mass as the measures of growth.
Keywords: Sørishavet; bryozoa; klimaendringer; marin biologi; mosdyr

De første skiturene i Antarktis - Barr, Susan (Snø & ski: årbok, 2007)
Keywords: Antarktis; ekspedisjoner; historie; logistikk

Variations in behavior and condition of a Southern Ocean top predator in relation to in situ oceanographic conditions - Biuw, Martin; Boehme, L.; Guinet, C.; Hindell, M.; Costa, D.; Charrassin, J.-B.; Roquet, F.; Bailleul, F.; Meredith, M.; Thorpe, S.; Tremblay, Y.; McDonald, B.; et al. (Proceedings of the National Academy of Sciences, 2007)
Responses by marine top predators to environmental variability have previously been almost impossible to observe directly. By using animal-mounted instruments simultaneously recording movements, diving behavior, and in situ oceanographic properties, we studied the behavioral and physiological responses of southern elephant seals to spatial environmental variability throughout their circumpolar range. Improved body condition of seals in the Atlantic sector was associated with Circumpolar Deep Water upwelling regions within the Antarctic Circumpolar Current, whereas High-Salinity Shelf Waters or temperature/salinity gradients under winter pack ice were important in the Indian and Pacific sectors. Energetic consequences of these variations could help explain recently observed population trends, showing the usefulness of this approach in examining the sensitivity of top predators to global and regional-scale climate variability.
Publisher: Proceedings of the National Academy of Sciences
Keywords: Sørishavet; marin biologi; oseanografi; sjøelefanter

Ross seal (Ommatophoca rossii) annual distribution, diving behaviour, breeding and moulting, off Queen Maud Land, Antarctica - Blix, Arnoldus Schytte; Nordøy, Erling S. (Polar Biology, 2007)
Six out of ten adult Ross seals that were tagged with Argos satellite-linked dive recorders off Queen Maud Land, just after the moult in February, provided data on location and diving activity throughout a year. Shortly after tagging, the animals headed 2,000 km north and stayed pelagic in the area south of the Antarctic Polar Front, until October when they went south into the pack-ice. Throughout the year they made about 100 dives a day, most to a depth of 100–300 m, the deepest dive on record being 792 m, while some dives were very shallow during their stay in the pack-ice. Most dives, outside the breeding and moulting period, lasted for 5–15 min throughout the year. This diving behaviour is consistent with feeding on mid-water fish, like Pleurogramma antarcticum, squid, and to some extent krill (Euphausia superba), when in the pack-ice, and myctophid fish and several species of squid, when in the open ocean. The nursing period was 13 days in mid-November, and moulting occurs in late January–early February, which is the period when sightings surveys for this species should be done.
Keywords: Sørishavet; marin biologi; pinnipedier; satellittsendere; seler; telemetri; zoologi

Norway and past International Polar Years—a historical account - Bones, Stian (Polar Research, 2007)
Surveying Norway’s role in past International Polar Years (IPYs), this essay by historian Stian Bones contributes to a broader understanding of Norway as a “polar nation”. He describes the strengths of Norway’s scientific traditions in the polar regions, and examines the varying motivations driving Norwegian involvement in the first three IPYs: 1882–83, 1932–33 and 1957–58 (also known as the International Geophysical Year).
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Norge; historie; polarområdene; vitenskap

Reproductive performance and organochlorine pollutants in an Antarctic marine top predator: The south polar skua - Bustnes, Jan O; Tveraa, Torkild; Varpe, Øystein; Henden, John A; Skaare, Janneche U (Environment International, 2007)
Keywords: Dronning Maud Land; forurensning; miljø; ornitologi; polarområdene; reproduksjon; økologi

Fra selfangstskuter til vitenskapelige ekspedisjonsskip. Svend Foyn og ishavsekspansjonen fra Sør-Norge - Christensen, Olav (Norsk sjøfartsmuseum. Årbok, 2007)
Publisher: Norsk sjøfartsmuseum Place: Oslo
Keywords: Carl Anton Larsen; Nordmenn; Sørishavet; Vestfold; ekspedisjoner; fangst; hvalfangere; hvalfangst; oppdagelsesreiser; polarområdene; vitenskap

National and institutional productivity and collaboration in Antarctic science: an analysis of 25 years of journal publications (1980–2004) - Dastidar, Prabir G. (Polar Research, 2007)
Journal publications on Antarctic science were analysed for a period of 25 years (1980–2004) through a set of scientometrics and network analysis techniques. The study is based on 10 942 records (research articles, review articles, letters, etc.) with the word fragment “antarc*” in the title published in 961 international, peer-reviewed journals and retrieved from Thomson Scientific’s Science Citation Index database. During the period under investigation, productivity increased threefold and there was a 13-fold increase in journal publications co-written by authors from different countries. The five nations with the highest output were the USA (with 26.7% of the total output), the UK (13.8%), Australia (9.7%), Germany (8.8%) and Italy (6.0%). The top five institutions in terms of journal publications were the British Antarctic Survey (972 publications), the Alfred Wegener Institute of Polar and Marine Research, Germany (475), the Australian Antarctic Division (312), the University of Tasmania, Australia (305), and the National Aeronautics and Space Administration, USA (293).
Keywords: Antarktis; dataanalyse; forskning; scientometri; tidsskriftspublikasjoner

Diversity and species distribution of polychaetes, isopods and bivalves in the Atlantic sector of the deep Southern Ocean - Ellingsen, Kari E.; Brandt, Angelika; Ebbe, Brigitte; Linse, Katrin (Polar Biology, 2007)
We examined deep-sea benthic data on polychaetes, isopods and bivalves from the Atlantic sector of the Southern Ocean. Samples were taken during the expeditions EASIZ II (1998), ANDEEP I and II (2002) (depth: 742-6,348 m). The range between sites varies from 3 to 1,900 km. Polychaetes (175 species in total) and isopods (383 species) had a high proportion of species restricted to one or two sites (72 and 70%, respectively). Bivalves (46 species) had a higher proportion of species represented at more sites. Beta diversity (Whittaker and Jaccard) was higher for polychaetes and isopods than for bivalves. The impact of depth on species richness was not consistent among groups; polychaetes showed a negative relationship to depth, isopods displayed highest richness in the middle depth range (2,000-4,000 m), whereas bivalves showed no clear relationship to depth. Species richness was not related to latitude (58-74 degrees S) or longitude (22-60 degrees W) for any group.
Keywords: Sørishavet; biodiversitet; flerbørstemarker; isopoder; marin biologi; muslinger; skjell; tanglus

Pan-African granulites of central Dronning Maud Land and Mozambique: a comparison within the East-African-Antarctic orogen - Engvik, Ane K; Elvevold, Synnøve; Jacobs, Joachim; Tveten, E; de Azevedo, S; Njange, F (Antarctica - a keystone in a changing world: online proceedings for the 10th International Symposium on Antarctic Earth Sciences, 2007)
Granulite-facies metamorphism is extensively reported in Late Neoproterozoic/Early Palaeozoic time during formation of the East-African-Antarctic orogen (EAAO). Metamorphic data acquired from the Pan-African orogen of central Dronning Maud Land (cDML) are compared with data from northern Mozambique. The metamorphic rocks of cDML are characterised by Opx±Grt-bearing gneisses and Sil+Kfs-bearing metapelites which indicate medium-P granulite-facies metamorphism. Peak conditions, which are estimated to 800-900ºC at pressures up to 1.0 GPa, were followed by near-isothermal decompression during late Pan-African extension and exhumation. Granulite-facies lithologies are widespread in northern Mozambique, and Grt+Cpx-bearing assemblages show that high-P granulitefacies conditions with PT reaching 1.55 GPa and 900ºC were reached during the Pan-African orogeny. Garnet is replaced by symplectites of Pl+Opx+Mag indicating isothermal decompression, and the subsequent formation of Pl+amphibole-coronas suggests cooling into amphibolite facies. It is concluded that high-T metamorphism was pervasive in EAAO in Late Neoproterozoic/Early Paleozoic time, strongly overprinting evidences of earlier metamorphic assemblages.
Keywords: Dronning Maud Land; geologi

På nåde over Antarktis : verdens lengste skitur : 4804 km - Gjeldnes, Rune (SEAL Adventure, 2007)
Keywords: Antarktis; geografi; oppdagelsesreiser; polarekspedisjoner; reiser; reiseskildringer

Polar Research evolves, and Norway and the IPY - Goldman, Helle V (Polar Research, 2007)
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Norge; Norsk Polarinstitutt; ekspedisjoner; forskning; polarområdene; vitenskap

Observasjoner av atmosfæriske parametere ved Troll-stasjonen i Antarktis - forskning og overvåkning basert på lange tidsserier. Fase 1 (2005/06) - NFR/NARE prosjekt 168908/S30 - Hansen, Georg Heinrich; Aspmo, Katrine; Berg, Torunn; Edvardsen, Kåre; Fiebig, Markus; Kallenborn, Roland; Lunder, Chris Rene; Nilsen, Tore; Schmidbauer, Norbert; Solberg, Sverre; Stebel, Kerstin; Wasseng, Jan; et al. (NILU, 2007)
Fra årsskifte 2006/2007 har den norske Antarktisstasjonen Troll (72º S, 2º E, 1270 m.o.h.) i Dronning-Maud-Land vært en helårsbemannet forsknings-, overvåkings- og servicestasjon. Dette åpnet for muligheten til å gjennomføre kontinuerlige målinger av en rekke viktige atmosfæriske parametre. I februar 2007 ble den nye NILU-atmosfære målestasjonen på Troll satt i gang. Måleprogrammet omfatter optiske, fysiske og kjemiske egenskaper av aerosoler, totalozon og UV-stråling, uorganisk og organisk forurensning inkludert tungmetaller som kvikksølv, samt meteorologiske parametre. Programmet omfatter også oppbyggingen av et luftflaskearkiv. Etter de første 6 månedene med den første Antarktisvinteren ser alle instrumenter ut til å være i meget god tilstand og levererkontinuerlig nye data. Disse analyseres for tiden, og de første resultatene vil bli publisert tidlig i 2008. Måleprogrammet finansieres i all hovedsak gjennom forskningsprogrammet NARE (Norwegian Antarctic Research Expeditions) ved Norsk polarinstitutt.
Publication Title: NILU Technical reports Volume: TR, 07/2007 Issue: NILU:105055
Keywords: Dronning Maud Land; Troll forskningsstasjon; miljøovervåking; målinger

Changes at Peter I Øy - Headland, Robert K (Polar Research, 2007)
Peter I Øy, a remote Norwegian territory, is one of the most rarely visited of the peri-Antarctic islands. Since the last Norwegian research visit, in 1987, approximately 10 tourist ships have been to the island, and about half of these have made landings. Where practical, reports have been sent to the Norwegian Polar Institute and other interested parties. I have made five visits, landing during four of them, while employed by Quark Expeditions to lecture on Antarctic history and geography aboard Kapitan Khlebnikov . My most recent visit, on 21 November 2006, demonstrated the continual geological erosion of the coast. In 2004 at Pingvinholet there was a splendid triple natural arch: the outer arch was formed by black basaltic deposits, and the inner one was capped by a stratum of red oxidized larva. The third arch was the result of a basalt flake slipping and propping itself against the middle column. The sea penetrated through all three arches so that it would have been possible, although reckless, to take a small boat through the largest of them. In late 2006, while sailing from South America to New Zealand near the Antarctic coast, I noted the entire inner section had collapsed. Only one large arch now remains and this no longer admits the sea. The collapse of both the cap of red larva and supporting pillar has formed a pile of rubble several metres above the sea.
Keywords: Peter I. Øy; geologi; turisme

Den Norske Antarktisekspedisjonen 1956-60 : Norway Station (Fimbul) - Henriksen, Hans-Martin (2007)
Keywords: Antarktistraktaten 1959; Den norske antarktisekspedisjonen 1956–1960; Det internasjonale geofysiske år 1957/58; Dronning Maud Land; IGY 1957-58; NAX; geologi; glasiologi; jordmagnetiske målinger; kartlegging; meteorologi; overvintring; tidevannsmålinger

Marine-sedimentary geology - Kuhn, Gerhard; Hillenbrand, Claus-Dieter; Hass, Christian; Lensch, Norbert; Forwick, Matthias; Daniel, Kristin; Kober, Martin; Krüger, Stefan; Petitat, Manuel; Veit, Andreas (The Expedition ANT-XXIII/4 of the Research Vessel Polarstern in 2006, 2007)
Dynamic behaviour of the West Antarctic ice sheet in the Amundsen Sea Embayment during the later quaternary climatic cycles, pliocene to quaternary palaeoceanography in the Southwest Pacific, and holocene climate history of Maxwell Bay, King George Island.
Keywords: Sørishavet; havnivåstigning; innlandsis; klimaendringer; marin geologi; oseanografi

De fire store : og hvordan de ledet sine menn - Kvam, Ragnar (Gyldendal, 2007)
De satte seg nesten uvirkelige mål. De skulle erobre de siste uoppdagede steder på kloden. Kan deres egenskaper og lederstil fortelle oss hvorfor noen lyktes bedre enn andre? Nansen var først ute. Skituren over Grønland hadde gitt ham ukuelig vågemot: Nå var målet Nordpolen. Siden ville Amundsen samme vei. Britene festet blikket på Antarktis. Først Schackleton, så Scott. Fire menn med store drømmer, sterk vilje, kraftig ego. Som vi vet, skulle ekspedisjonene føre til triumf . og tragedie. I sin nye bok skildrer Ragnar Kvam jr. noen av polarhistoriens mest dramatiske kapitler. Han setter søkelyset på hvem de er, disse fire lederskikkelsene. Hva var det som drev dem? Hvordan ledet de sine menn? Kan deres egenskaper og lederstil fortelle oss hvorfor noen lyktes bedre enn andre? Gjennom fire fortellinger får leseren et fascinerende portrett av "de fire store", av deres evne til å skape motivasjon og lagånd, av deres psykiske utrustning og evne til å takle ekstreme situasjoner. Kvams mål er å kaste nytt lys over det som i siste instans virkelig bestemmer deres måte å lede på deres personlighet.
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; biografier; polarekspedisjoner; polarhistorie

Modulation of the bipolar seesaw in the Southeast Pacific during Termination 1 - Lamy, Frank; Kaiser, Jérôme; Arz, Helge W; Hebbeln, Dierk; Ninnemann, Ulysses; Timm, Oliver; Timmermann, Axel; Toggweiler, J R (Earth and Planetary Science Letters, 2007)
The termination of the last ice age (Termination 1; T1) is crucial for our understanding of global climate change and for the validation of climate models. There are still a number of open questions regarding for example the exact timing and the mechanisms involved in the initiation of deglaciation and the subsequent interhemispheric pattern of the warming. Our study is based on a well-dated and high-resolution alkenone-based sea surface temperature (SST) record from the SE-Pacific off southern Chile (Ocean Drilling Project Site 1233) showing that deglacial warming at the northern margin of the Antarctic Circumpolar Current system (ACC) began shortly after 19,000 years BP (19 kyr BP). The timing is largely consistent with Antarctic ice-core records but the initial warming in the SE-Pacific is more abrupt suggesting a direct and immediate response to the slowdown of the Atlantic thermohaline circulation through the bipolar seesaw mechanism. This response requires a rapid transfer of the Atlantic signal to the SE-Pacific without involving the thermal inertia of the Southern Ocean that may contribute to the substantially more gradual deglacial temperature rise seen in Antarctic ice-cores. A very plausible mechanism for this rapid transfer is a seesaw-induced change of the coupled ocean–atmosphere system of the ACC and the southern westerly wind belt. In addition, modelling results suggest that insolation changes and the deglacial CO2 rise induced a substantial SST increase at our site location but with a gradual warming structure. The similarity of the two-step rise in our proxy SSTs and CO2 over T1 strongly demands for a forcing mechanism influencing both, temperature and CO2. As SSTs at our coring site are particularly sensitive to latitudinal shifts of the ACC/southern westerly wind belt system, we conclude that such latitudinal shifts may substantially affect the upwelling of deepwater masses in the Southern Ocean and thus the release of CO2 to the atmosphere as suggested by the conceptual model of [Toggweiler, J.R., Rusell, J.L., Carson, S.R., 2006. Midlatitude westerlies, atmospheric CO2, and climate change during ice ages. Paleoceanography 21. doi:10.1029/2005PA001154].
Keywords: Sørishavet; Sørishavsstrømmen; havstrømmer; oseanografi; paleoklimatologi

The Norwegian-British-Swedish Expedition (NBSX) to Antarctica 1949-52 - science and security - Lewander, Lisbeth (Berichte zur Polar- und Meeresforschung = Reports on Polar and Marine Research, 2007)
The most frequent way of summarizing the story of the NBSX may be illustrated by the following few paragraphs. Shortly after the Second World War had ended Norway took a leading role in organising the first international expedition to Antarctica. Norway was in charge of meteorology and surveying, Great Britain was responsible for geology and Sweden was entrusted with glaciology. The British RAF assisted in air operations 1949/50 with five officers (in finding a landing place for the expedition as well as for meteorological investigations, one officer remained as radio operator), the Norwegian Wideröe Company assisted in 1950/51 (air surveying) and the Swedish Air Force in 1951/52, with 6 officers (originally for reconnaissance of ice conditions as well as being prepared for emptying the base). The Norwegian sealer Norsel landed the party and the whaler Thorshövdi assisted as well for transport of dogs aircraft and weasels. For general overviews and details of the scientific achievements, logistics and perspectives of international cooperation there are several works available.
Publisher: Alfred-Wegener-Institut für Polar- und Meeresforschung Place: Bremerhaven
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

Kap. 4. Is og snø smelter. Kap. 5. Øyer og lavland kan drukne - Mathismoen, Ole; Ulvestad, Knut Ola (bildered.); Lie, Maya (bildered.) (Klima : hva skjer?, 2007)
Keywords: Antarktis; Sørishavet; drivhuseffekten; global oppvarming; havnivåstigning; klimaendringer

Henrik Bull, the Antarctic Exploration Committee and the first confirmed landing on the Antarctic continent - McConville, Andrew (Polar Record, 2007)
Publisher: Cambridge University Press
Keywords: Antarktis; Carsten Egeberg Borchgrevink; D/S Antarctic; Henrik Johan Bull; Kapp Adare; Leonard Kristensen; Rosshavet; Victoria Land; ekspedisjoner; forskning; første landgang; oppdagelsesreiser

The Southern Ice Ocean Model Intercomparison Project (SIOMIP) - O'Farrell, Siobhan (Ice and climate news, 2007)
Keywords: Sørishavet; forskning; glasiologi; havis

Polaroppdraget - Paulsen, Øystein S (Forsvarets forum, 2007)
Keywords: Dronning Maud Land; ekspedisjoner; fly; logistikk

A new surface accumulation map for western Dronning Maud Land, Antarctica, from interpolation of point measurements - Rotschky, Gerit; Holmlund, Per; Isaksson, Elisabeth; Mulvaney, Robert; Oerter, Hans; Van Den Broeke, Michiel R; Winther, Jan-Gunnar (Journal of Glaciology, 2007)
As a result of intensive field activities carried out by several nations over the past 15 years, a set of accumulation measurements for western Dronning Maud Land, Antarctica, was collected, based on firn-core drilling and snow-pit sampling. This new information was supplemented by earlier data taken from the literature, resulting in 111 accumulation values. Using Geographical Information Systems software, a first region-wide mean annual snow-accumulation field was derived. In order to define suitable interpolation criteria, the accumulation records were analyzed with respect to their spatial autocorrelation and statistical properties. The resulting accumulation pattern resembles well- known characteristics such as a relatively wet coastal area with a sharp transition to the dry interior, but also reveals complex topographic effects. Furthermore, this work identifies new high-return shallowdrilling sites by uncovering areas of insufficient sampling density.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; glasiologi

Til Antarktis for å simulere fremtiden - Sirevaag, Anders (AKA : tverrfaglig studentlektyre, 2007)
Publisher: Studentene ved Universitetet i Bergen Place: Bergen
Keywords: Antarktis; klimaendringer; populærvitenskap

A seismo-stratigraphic analysis of glaciomarine deposits in the eastern Riiser-Larsen Sea (Antarctica) - Solli, Kenneth; Kuvaas, Berit; Kristoffersen, Yngve; Leitchenkov, German; Guseva, J; Gandjukhin, V (Marine Geophysical Researches, 2007)
Keywords: Sørishavet; innlandsis; kontinentalsokkel; seismologi; stratigrafi

Seismic morphology and distribution of inferred glaciomarine deposits along the East Antarctic continental margin, 20°E–60°E - Solli, Kenneth; Kuvaas, Berit; Kristoffersen, Yngve; Leitchenkov, German; Guseva, J; Gandjukhin, V (Marine Geology, 2007)
Keywords: Antarktis; innlandsis; isstrøm; kontinentalstiging; marin geologi; morfologi; sedimentologi; seismologi

Hval og politikk : hvalfangstnæringens rolle i utformingen av den norske hvalfangstpolitikken på 1950-tallet - Thorsen, Eivind; Kolle, Nils (Universitetet i Bergen, 2007)
Siste halvdel av 1950-tallet var en viktig periode i norsk hvalfangst. Norge, som tidligere hadde vært den dominerende hvalfangstnasjonen, var som resultat av hard konkurranse kommet på defensiven i forhold til de andre hvalfangstnasjonene. Den høye hvaloljeprisen, som blant annet var forårsaket av Europas fettbehov i kjølvannet av den andre verdenskrig, resulterte i at nye nasjoner etter krigen engasjerte seg i hvalfangst. For å sikre seg en størst mulig andel av totalkvoten ønsket Sovjetunionen og Japan nå å foreta en kraftig utbygging av sine fangstflåter, noe som ville gjøre situasjonen enda vanskeligere for den norske hvalfangstnæringen. Det var av største viktighet at denne ekspansjonen ble stoppet, siden dette spørsmålet i norske hvalfangstkretser ble oppfattet som et være eller ikke være for norsk hvalfangst. De norske hvalfangstselskapene startet derfor en kampanje for å få regjeringen til å stanse de to landenes utbyggingsplaner. Mitt hovedfokus i denne oppgaven vil være å belyse hvalfangstnæringens rolle i utformingen av den norske hvalfangstpolitikken på 1950-tallet. For å kunne gi et svar på dette spørsmålet har jeg tatt for meg to av hvalfangstpolitikkens viktigste saker dette tiåret. Den første dreier seg om den nevnte kampen for å stanse Sovjetunionens og Japans ekspansjonsplaner, mens den andre dreier seg om kampen for en ordning med nasjonale kvoter. En studie av disse to sakene gir også innsyn i næringen som helhet. I tillegg til å kartlegge hvalfangstnæringens politiske innflytelse vil det også være viktig å gi en fremstilling av utviklingen innen hvalfangstreguleringen i denne perioden, altså siste halvdel av 1950-tallet. Med begrepet norsk hvalfangstpolitikk, mener jeg den politikken regjeringen utformet og som blant annet ble presentert på de årlige møtene i Den internasjonale hvalfangskommisjonen (IWC). For å kunne gi et godt svar på problemstillingen er det nødvendig å besvare flere underliggende spørsmål. Hvalfangstselskapene organiserte seg tidlig gjennom dannelsen av Norges Hvalfangstforbund. Dette var en organisasjon som kjempet for at hvalfangstredernes interesser ble ivaretatt. Hvalfangstrederne var i tillegg representert i Hvalrådet. Dette var et statlig organ som hadde en rådgivende funksjon i regjeringens utarbeidelse av den norske hvalfangstpolitikken. Følgende spørsmål blir derfor viktige i mitt arbeid: Hvilken rolle spilte Norges Hvalfangstforbund i utformingen av den norske hvalfangstpolitikken? Hvordan opererte næringens representanter for å få gjennomslag for sine interesser i Hvalrådet? Det vil også være nødvendig å kartlegge sammenhengen mellom Hvalrådet og regjeringen. I hvilken grad var Hvalrådets uttalelser utslagsgivende for den endelige norske hvalfangstpolitikken? Bortsett fra tiden da Norge stod utenfor Den internasjonale hvalfangstkonvensjonen, sendte landet hvert år en delegasjon til kommisjonens årlige møter. Det vil være viktig å undersøke i hvilken grad næringen var representert i disse delegasjonene. Møtte den norske delegasjonen med bundet mandat, eller hadde den en viss frihet til å forhandle? Mot slutten av oppgaven ønsker jeg å se komparativt på hvalfangstnæringens politiske innflytelse i forhold til landbruket og fiskerinæringen i den samme perioden. Oppnådde hvalfangstnæringen større politisk innflytelse sammenliknet med disse næringene, og hva skyldtes i tilfelle dette?
Publication Title: Institutt for arkeologi, historie, kultur- og religionsvitenskap Volume: M.Sc. Issue: HIS350
Keywords: Sørishavet; historie; hvalfangst; pelagisk; politikk

Det første forskningstoktet til Antarktis - Tofte, Kari Østervold (Polaråret: et magasin om det internasjonale polaråret 2007-2008, 2007)
Keywords: Sørishavet; forskning; marin biologi

Quantitative analysis of soft-bottom molluscs in the Bellingshausen Sea and around Peter I Island - Troncoso, Jesús S; Aldea, Cristian; Arnaud, Patrick; Ramos, Ana; García, Francisco (Polar Research, 2007)
Macrobenthic soft-bottom molluscs were sampled in 30 stations located in the Bellingshausen Sea at depths ranging from 90 to 3304 m. The samples were collected using a quantitative grab box-corer during the cruises BENTART 03, from 24 January to 3 March 2003, and BENTART 06, from 2 January to 16 February 2006. Molluscs represent 1074 specimens belonging to 62 species of Polyplacophora, Gastropoda, Bivalvia and Scaphopoda. The bivalve Cyamiocardium denticulatum was the most abundant species (448 specimens). The abundance per station varied between 1 and 446 specimens. The Shannon–Wiener diversity index ranged between one specimen and 2.36, the Pielou evenness index ranged between 0.00 and 1 and species richness ranged from 1 to 14 species. Diversity showed great variations at different stations. After multivariate analysis (cluster analysis and nonmetrical multidimensional scaling) based on Bray–Curtis similarities, we were able to separate two principal clusters. The first cluster groups together species from shallower bottoms near Peter I Island and the Antarctic Peninsula, and the second cluster groups together species from deeper bottoms in the Bellingshausen Sea. The combination of environmental variables with the highest correlations with faunistic data was that of depth and coarse sand at the surface.
Keywords: Peter I. Øy; Sørishavet; bløtdyr; marin biologi; marine økosystemer; mollusker; oseanografi

Widerøe kartlegger i Antarktis - Widerøe, Turi (Perspektiv, 2007)
Keywords: Antarktis; Dronning Maud Land; Lars Christensen; Norvegia ekspedisjoner; flyhistorie; hvalfangst; kartlegging

International Workshop on Antarctic Sea-Ice Thickness, Hobart, Tasmania, 5-7 July 2006 - Worby, Tony; Ackley, Steve (Ice and climate news, 2007)
Keywords: Sørishavet; glasiologi; havis; konferanser